Quality of banana fruit produced in different locations (Greenhouse and open air) of the Canary Islands - Damatto Junior, Erval Rafael; Bôas, Roberto Lyra Villas [UNESP]; Leonel, Sarita [UNESP]; Cabrera, Juan Cabrera; Saucco, Victor Galan (My University, 2010)
This work aimed to evaluate fruit quality and nutrient content of Cavendish banana cultivars produced under different greenhouse covers in Tenerife Island (Spain) and compare them with other bananas production regions in the island. Observation on fruit quality under greenhouse were carried out in the experimental station of Pajalillos of ICIA - Instituto Canario de Investigaciones Agrarias on a plot planted with in vitro plants of two cultivars (‘Grand Nain’ and ‘Gruesa’) in their fifth crop cycle, cultivated under four greenhouse covers: Celloclim (thermic plastic), 20 × 10 mesh, white mesh and 16 × 10 mesh. Data were also collected in open air cultivation in 3 different locations of Tenerife: Cueva del Polvo, Hoya Meleque and Canaria Forestal. Nutrients levels in the dry mass of ‘Gruesa’ and ‘Grand Nain’ banana leaf did not show differences between cultivars nor among different greenhouse covers. The parameters analysed related to fruit quality were not also influenced by covers or cultivars and nor relevant differences were also detected between open air condition and greenhouse cultivation.
Keywords: Cultivars; Musa sp.; Nutrients; Post harvest; Protected cultivation